Lightning Potential Index performances in multimicrophysical cloud‐resolving simulations of a back‐building mesoscale convective system: The Genoa 2014 event. Issue 8 (25th April 2017) - Lagasio, M.; Parodi, A.; Procopio, R.; Rachidi, F.; Fiori, E.
Abstract: Severe weather events are responsible for hundreds of fatalities and millions of euros of damage every year on the Mediterranean basin. Lightning activity is a characteristic phenomenon of severe weather and often accompanies torrential rainfall, which, under certain conditions like terrain type, slope, drainage, and soil saturation, may turn into flash flood. Building on the existing relationship between significant lightning activity and deep convection and precipitation, the performance of the Lightning Potential Index, as a measure of the potential for charge generation and separation that leads to lightning occurrence in clouds, is here evaluated for the V‐shape back‐building Mesoscale Convective System which hit Genoa city (Italy) in 2014. An ensemble of Weather Research and Forecasting simulations at cloud‐permitting grid spacing (1 km) with different microphysical parameterizations is performed and compared to the available observational radar and lightning data. The results allow gaining a deeper understanding of the role of lightning phenomena in the predictability of V‐shape back‐building Mesoscale Convective Systems often producing flash flood over western Mediterranean complex topography areas. Moreover, they support the relevance of accurate lightning forecasting for the predictive ability of these severe events. Key Points: Lightning activity is a typical phenomenon of severe weather characterized by strong convection LPI is a measure of the potential for charging and separation that leads to lightning in clouds Lightning plays a role in detecting and nowcasting flash flood events